Software Learning Tool to Calculate Isotope Pattern for Chemistry Area of Study - Kamalrudin, Massila; Soong, Hoong Cheng; Abdul-Aziz, Azlianor; Sulong, Muhammad Suhaizan (2008)
This article describes the anticipated software learning tool to calculate the isotope pattern for educational purposes. Despite the availability of the mass spectrometer to classify the existence of the isotopes from the particular elements, the projected software is indeed practical, beneficial and constructive for the academic learners as well for the intellectual researchers for rapidly defining the numbers of the possibility isotope patterns obtainable from a substance(chemical compound) for example methane (CH2). Hence, with the mathematical application (Cartesian Products) and the fundamental knowledge of chemistry that facilitate the calculations are feasible to obtain the isotope patterns without the aid of the mass spectrometer. For instance, the intended calculator called as Theoretical Isotope Generator (TIG) is fairly to be a calculation engine as well that is proficient to retrieve the information of the mass (atomic/molecular weight) from the substance specified based from the isotope patterns available. In conjunction of the patterns attained, the current mass spectrometer defines the acknowledged atomic isotopes of each identified elements which will be predefined for the software learning tools in order to regain the calculation for the molecular isotope patterns.